Study on the effect of different adhesives on properties of hybrid plywood from coconut and rubberwood / Mohammad Fahamy Ismail, Siti Noorbaini Sarmin and Ahmad Sardey Idris - Ismail, Mohammad Fahamy; Sarmin, Siti Noorbaini; Idris, Ahmad Sardey (2011)
Shortage of wood as a raw material has forced wood-based industries to find alternative local raw materials. This study was undertaken to determine the properties of hybrid plywood from coconut and rubberwood veneer of different adhesives used and glue-spread rate. Experimental plywood panel from coconut veneers bonded with Polyvinyl acetate (PVAc) and Phenol formaldehyde (PF) were produced with adhesive spread levels; 180g/m2 and for single glueline. The physical and mechanical properties were then accessed. The results show that hybridisation of coconut with rubberwood improves some properties of plywood, such as bending strength, tensile shear strength, water absorption and thickness swelling, and density. The tensile shear strength was higher in panel bonded with PF at 180g/m2 compare with PVAc. The panels glued with PF using 180g/m2 spread level showed better in MOR and MOE compare with plywood bonded using PVAc. Density of panel manufactured using PVAc using l80g/m2 spread level was higher compare with panel bonded with PF. Water absorption and thickness swelling rate were slightly lower for plywood manufactured using PF at 180g/m2.